Characteristics of a COVID-19 Cohort With Large Vessel Occlusion: A Multicenter International Study. Issue 6 (7th June 2022) - Jabbour, Pascal; Dmytriw, Adam A.; Sweid, Ahmad; Piotin, Michel; Bekelis, Kimon; Sourour, Nader; Raz, Eytan; Linfante, Italo; Dabus, Guilherme; Kole, Max; Martínez-Galdámez, Mario; Nimjee, Shahid M.; et al.
Abstract : BACKGROUND: The mechanisms and outcomes in coronavirus disease (COVID-19)–associated stroke are unique from those of non–COVID-19 stroke. OBJECTIVE: To describe the efficacy and outcomes of acute revascularization of large vessel occlusion (LVO) in the setting of COVID-19 in an international cohort. METHODS: We conducted an international multicenter retrospective study of consecutively admitted patients with COVID-19 with concomitant acute LVO across 50 comprehensive stroke centers. Our control group constituted historical controls of patients presenting with LVO and receiving a mechanical thrombectomy between January 2018 and December 2020. RESULTS: The total cohort was 575 patients with acute LVO; 194 patients had COVID-19 while 381 patients did not. Patients in the COVID-19 group were younger (62.5 vs 71.2; P < .001) and lacked vascular risk factors (49, 25.3% vs 54, 14.2%; P = .001). Modified thrombolysis in cerebral infarction 3 revascularization was less common in the COVID-19 group (74, 39.2% vs 252, 67.2%; P < .001). Poor functional outcome at discharge (defined as modified Ranklin Scale 3-6) was more common in the COVID-19 group (150, 79.8% vs 132, 66.7%; P = .004). COVID-19 was independently associated with a lower likelihood of achieving modified thrombolysis in cerebral infarction 3 (odds ratio [OR]: 0.4, 95% CI: 0.2-0.7; P < .001) and unfavorable outcomes (OR: 2.5, 95% CI: 1.4-4.5; P = .002). CONCLUSION: COVID-19 was an independent predictor of incomplete revascularization and poor outcomes in patients with stroke due to LVO. Patients with COVID-19 with LVO were younger, had fewer cerebrovascular risk factors, and suffered from higher morbidity/mortality rates. Abstract :